Unveiling the underlying mechanism of nitrogen fixation by a new class of electrocatalysts two-dimensional TM@g-C4N3 monosheets - Wang, Xiaolin; Yang, Li-Ming (Applied surface science, 2022)
Four new electrocatalysts TM@g-C4N3 (TM = V, Tc, Os, Pt) of NRR obtained from high-throughput screening and first-principles calculations of 3d, 4d and 5d transition metal series. [Display omitted] •The hierarchical high-throughput screening method was developed and applied.•The most active catalyst is V@g-C4N3 with onset potential as low as -0.37 V.•ΔEads(*N2) can be an descriptor to characterize the activity of catalysts.•The evolution trend of catalytic activity is consistent with that of d-band center. The potential of TM atoms embedded g-C4N3 as a new class of electrocatalysts (TM@g-C4N3, TM = 3d, 4d and 5d transition metal) towards nitrogen reduction reaction (NRR) were systematically investigated through the combination of high-throughput screening and first-principles calculations. Among 30 candidate materials, TM@g-C4N3 (TM = V, Tc, Os, Pt) exhibited the highest activity for electrocatalytic N2 reduction to produce NH3. Particularly, V@g-C4N3 is identified as the most active catalyst for NRR with onset potential of −0.37 V. Interestingly, a volcano curve between Uonset (onset potential) and ΔEads(*N2) (the adsorption energy of N2) is established, and thus ΔEads(*N2) can be used as a descriptor to characterize the activity of catalysts. Among all investigated catalysts, the lowest onset potential of V@g-C4N3 can be attributed to its moderate adsorption energies for N2. After in-deep analysis of the intrinsic properties of the four catalysts, we found that the increasing order of catalytic activity is consistent with the increasing order of d-band center (εd) of the four catalysts. In addition, the excellent thermal stability of the four catalysts is verified via simulated annealing at 500 K for 10 ps. Furthermore, three catalysts TM@g-C4N3 (TM = V, Tc, Pt) demonstrate good selectivity. Therefore, V@g-C4N3 is a promising electrocatalyst for NRR. Our work opens the way for g-C4N3 as a new type of support to construct efficient single-atom catalyst for electrocatalytic ammonia synthesis. The predicted TM@g-C4N3 catalysts will provide useful guidance for experimental synthesis and rational design of catalysts in future.